2018
DOI: 10.1007/s00604-018-2980-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in nanomaterial based optical biosensing and bioimaging of apoptosis via caspase-3 activity: a review

Abstract: Caspase-3 plays a vital role in intrinsic and extrinsic pathways of programed cell death and in cell proliferation. Its detection is an important tool for early detection of some cancers and apoptosis-related diseases, and for monitoring the efficacy of pharmaceuticals and of chemo- and radiotherapy of cancers. This review (with 72 references) summarizes nanomaterial based methods for signal amplification in optical methods for the determination of caspase-3 activity. Following an introduction into the field, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 71 publications
3
33
0
Order By: Relevance
“…Furthermore, Bax could also downregulate apoptosis and the mitochondrial membrane in mitochondria as a pro-apoptotic gene [33]. Caspases, such as cleaved caspase-3 and caspase-9, comprise a family of cysteine proteases that contribute to apoptosis and ultimately cell death [34,35], and Bax and Bcl2 are effective factors for the downstream activation of caspase protein [36]. In the present study, we found that Bax and active caspase-3/-9 were highly expressed, whereas Bcl-2 was decreased in AGS cells treated with vortioxetine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bax could also downregulate apoptosis and the mitochondrial membrane in mitochondria as a pro-apoptotic gene [33]. Caspases, such as cleaved caspase-3 and caspase-9, comprise a family of cysteine proteases that contribute to apoptosis and ultimately cell death [34,35], and Bax and Bcl2 are effective factors for the downstream activation of caspase protein [36]. In the present study, we found that Bax and active caspase-3/-9 were highly expressed, whereas Bcl-2 was decreased in AGS cells treated with vortioxetine.…”
Section: Discussionmentioning
confidence: 99%
“…Once caspase‐3 is activated, apoptosis occurs. Importantly, as a proteolytic enzyme, caspase‐3 activity is mostly based on the presence of a specific cleavage fragment peptide (Khalilzadeh et al ; Lincoln et al ). Our Western blotting analysis results showed that cleaved caspase‐3 was significantly upregulated in the etoposide‐induced group compared to that in the untreated group.…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 and BT-20 cells were seeded in a 96-well plate at density15 × 10 3 for 24, and 48 h, treated with different concentrations of MT (i.e., 5, 10, 20, 30 and 40 µM) as five groups including (a), (b), (c), (d) and (d) described at section (2.9.1.) and then incubated for 24 and 48 h. Finally, cleavage of the caspase-3 substrate (N-acetyl-DEVD-p-nitroaniline) [42] was monitored by measuring the fluorescent density at emission and excitation wavelengths of 535 nm and 485 nm, respectively. Data were obtained from two independent experiments.…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%